2017
DOI: 10.1007/s11120-017-0450-3
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of Psb27 from Arabidopsis thaliana determined at a resolution of 1.85 Å

Abstract: Proper biogenesis and maintenance of photosynthetic thylakoid membrane complexes are essential for the photosynthetic light reactions. A thylakoid lumenal protein, Psb27, plays a vital role in assembly or/and maintenance of photosystem II (PSII). In cyanobacteria, it is a small lipoprotein docked to the lumenal side of PSII, and functions in the assembly of the Mn4Ca cluster and in the PSII repair cycle. However, Psb27 from Arabidopsis thaliana is not a lipoprotein, and it is involved in PSII repair and acclim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…How Does Psb27 Facilitate Photoactivation? It has been shown that Psb27 is the vital player in PSII repair and assembly of the Mn 4 CaO 5 cluster of PSII that provides greater accessibility to the site of Mn-cluster assembly (32,33,36,(47)(48)(49). We find that Psb27 facilitates the photoactivation of the WOC in a more complex manner than simply displacing extrinsic polypeptides from apo-PSII.…”
Section: Discussionmentioning
confidence: 64%
“…How Does Psb27 Facilitate Photoactivation? It has been shown that Psb27 is the vital player in PSII repair and assembly of the Mn 4 CaO 5 cluster of PSII that provides greater accessibility to the site of Mn-cluster assembly (32,33,36,(47)(48)(49). We find that Psb27 facilitates the photoactivation of the WOC in a more complex manner than simply displacing extrinsic polypeptides from apo-PSII.…”
Section: Discussionmentioning
confidence: 64%
“…It has been shown that Psb27 is the vital player in PSII repair and assembly of the Mn4CaO5 cluster of PSII that provides greater accessibility to the site of Mn-cluster assembly (31,32,35,(46)(47)(48). We find that Psb27 facilitates the photoactivation of the WOC in a more complex manner than simply displacing extrinsic polypeptides from apo-PSII.…”
Section: How Does Psb27 Facilitate Photoactivation?mentioning
confidence: 63%
“…These inactive Psb27-PSII complexes are deficient in the Mn 4 CaO 5 cluster and three extrinsic subunits: PsbO, PsbV, and PsbU. The structure of Psb27 has been solved by both solution NMR (41,42) and X-ray crystallography (43,44), and its association with PSII assembly intermediate has been studied by chemical cross-linking analysis and mass spectrometry (45)(46)(47)(48). These studies suggested that Psb27 binds to the large extrinsic E-loop of CP43 at the luminal side; however, there are discrepancies regarding the detailed binding sites of Psb27 in PSII (45)(46)(47)(48).…”
Section: Significancementioning
confidence: 99%